Kajian Dosis Pupuk Kandang Kambing Dan Komposisi Media Tanam Terhadap Pertumbuhan Dan Hasil Tanaman Okra Merah - Widyastuti, Lina Ayu; Priyono, Priyono; Sudalmi, Endang Sri (Innofarm:Jurnal Inovasi Pertanian, 2020)
Research on "Study of Doses of Goat Manure and Composition of Planting Media on Growth and Yield of Red Okra Plants (Abelmoschus esculentus L. Moench)"has been carried out from March 20, 2020 to June 17, 2020 in Jenak Hamlet, Sidolaju Village, Widodaren District, Regency Ngawi withhaaheight of about 50-100 meterssaboveeseaalevel.This reserch aims to: (1) to determine the study of goat manure doses on the growth and yield of red okra plants (2) to determine the study of theecompositionnofftheeplantinggmedia on the growth and yield of okra red plants and (3) to determine the effect of the interaction of goat manure doses and the composition of the growing media on the growth and yield of red okra plants.The design used was a factorial Completely Randomized Design (CRD) consisting of 2 with 3 replications. The first factor is the dose of goat manure which includes: D1: Dose of goat manure 375 g / plant, D2: Dose of goat manure 750 g / plant. D3: Dose of goat manure 1125 g / plant. Theeseconddfactorrisstheecompositionnofftheeplanting medium including: M1n:nSoil,nM2:nSoill+hHuskkCharcoal,mM3 :sSoil + Sand, M4: Soil + Husk Charcoal + Sand. Dataaweremanalyzeddusing Variance Analysis,nwhich was followeddby Honest Real Difference Testtat 5% real level.The resultssshoweddthat (1) Dose treatment of goat manureehadaa very significantteffectton yield only on the dry weight of seeds per plant. The best treatment was obtained at a dose of goat manure 750 g / plant (D2) which produced the highest weight of dry seeds per plant, (2) Theetreatmenttof media composition hadnanverynsignificanteeffectoon plant height, number of leaves, number of fruits per plant, number of fruits per harvest, fruit fresh weight and seed dry weight per plant. The best treatment was obtained on the composition of the planting medium (M2) which had the highest yield on plant height, number of leaves, number of fruits per plant, number of fruits per harvest, dry weight of seeds per plant. While the composition of the planting medium (M4) produced the highest yield on fresh weight. fruit, (3) there was no interaction between the dose of goat manure and the composition of the planting medium.Â Â